The Extent to which Arabic Teachers in Al Balqa Governorate Possess the Skill to Use Interactive Whiteboards - Abeer Olaimat; Adab Al-Saud; Eman Al-Hussien (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
This study aims to find out the degree to which Arabic language teachers at public schools in Al-Balqa Governorate possess the skills to use interactive whiteboards from their perspective in the light of some variables. The study sample consisted of (90) teachers, chosen randomly. A descriptive approach was used, where a questionnaire consisting of (34) items was prepared and achieved valid and reliable means that permit its usage. The items were distributed to three domains of interactive whiteboard skills. The results of the study show that the degree to which Arabic teachers possess the skills to use interactive whiteboards was moderate. There were no statistically significant differences in interactive whiteboard skills due to gender, directorate or years of experience. There were statistically significant differences due to the educational qualification, however. The study recommends to conduct special training programs to equipe practitioner teachers with skills of using interactive whiteboard and its employment in their teaching, and to include it in future student teachers' prepaeration programs.